The Relationship of Nutrition Extension Through Monopoly Game Media With Knowledge And Attitudes About Balanced Nutrition in Elementary School 03 Children in Pasir Village, Tripe Jaya District. Gayo Lues Regency, 2022 - Mutia Nauli (Institute of Computer Science (IOCS), 2022)
The purpose of the study was to determine the relationship of nutrition counseling through the media of monopoly game to knowledge and attitudes about balanced nutrition in SDN 03 students in Pasir Village, Tripe Jaya District, Gayo Lues Regency in 2022. This type of research is a quantitative research (analytic survey) with a cross sectional approach. Location This research was conducted at SDN 03 Pasir Village, Tripe Jaya District, Gayo Lues Regency. The population in this study were taken from 2 classes at SDN 03, 15 students were sampled from class IV, and 15 students were taken from class V. The population technique in this study was non-probability sampling. The results showed that from 30 respondents that the majority of good knowledge as many as 15 respondents (50%). And the majority of children's nutritional attitudes in the very high category were 15 respondents (50%). This shows that nutrition counseling is closely related to knowledge of children's nutritional attitudes in understanding the importance of healthy food. Based on research conducted at SDN 03 Gayo Lues on the Relationship of Nutrition Extension Through Monopoly Game Media with Knowledge and Attitudes About Balanced Nutrition in Children at SDN 03 in Pasir Village, Tripe Jaya District, Gayo Lues Regency in 2022, the following conclusions can be drawn : The majority of children's knowledge about balanced nutrition at SDN 03 Gayo Lues, Tripe Jaya District, Gayo Lues Regency in 2022 is in the good category